Penerapan Diet Hipertensi pada Masyarakat Kelurahan Legok - Ariyanto Ariyanto; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2022)
Hypertension is one of the main problems in society in Indonesia and the world. It is estimated that around 80% of the increase in hypertension cases mainly occurs in developing countries in 2025 from a total of 639 million cases in 2000. This number is estimated to increase to 1.15 billion cases in 2025. This prediction is based on the number of people with hypertension and current population growth. The initial survey in January 2021, a survey conducted on one resident said he was still accustomed to an unhealthy lifestyle such as frequently consuming fatty foods, coconut milk, fried foods, smoking habits in men, lack of exercise and lack of understanding how to prevent hypertension. The purpose of this service is so that the community understands how to implement the Hypertension Diet in the Legok Village community, Jambi City. This service is carried out during the even semester from March-August 2021 at RT 037 Kel. Legok Danau Sipin, 15 participants participated. The method used is lecture, discussion and question and answer with leaflet and module media, physical examination tool is Tensimeter. The results of the activity obtained that all participants were able to understand how to apply the hypertension diet. Participants will also try to maintain/regulate eating patterns, avoid stress, also do physical activities and check blood pressure regularly